Platelet Profile in Patients with Status Asmaticus in Kebumen - Juwariyah, Juwariyah; Arjana, Adika Zhulhi; Rahayu, Ester Tri; Rosita, Linda; Irfan, Mohammad Rozan (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
BACKGROUND: Asthma has been considered as type 1 hypersensitivity disease, but actually asthma involves a variety of inf lammatory factors.Based on pro-inf lammatory cells, asthma is classified into eosinophilic, non-eosinophilic, neutrophilic, and non-neutrophilic. Platelet plays a role inÂ  pathophysiology of asthma through inf lammation. However, platelet profile in patients with asthma have not been established.OBJECTIVE: to determine the platelet indices of patients with status asmaticus of different phenotypes.METHODS: a cross-sectional study was conducted among a minimum sample size of 67 patients. Data were collected from medical records of patients in RSUD Kebumen. Platelet indices included mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT).RESULTS: There was no significant difference in the value of MPV and PDW in patients with eosinophilic and neutrophilic asthma (p> 0.05). But,there was a significant difference in PCT between the two groups (P <0.05)CONCLUSION: There was difference only in plateletcrit (PCT) between patients with eosinophilic and netrophilic asthma.